2021
DOI: 10.3389/fnhum.2021.728151
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Language and Domain-General Processing in Neurotypicals and Individuals With Aphasia — A Functional Near-Infrared Spectroscopy Pilot Study

Abstract: Brain reorganization patterns associated with language recovery after stroke have long been debated. Studying mechanisms of spontaneous and treatment-induced language recovery in post-stroke aphasia requires a network-based approach given the potential for recruitment of perilesional left hemisphere language regions, homologous right hemisphere language regions, and/or spared bilateral domain-general regions. Recent hardware, software, and methodological advances in functional near-infrared spectroscopy (fNIRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 121 publications
1
4
0
Order By: Relevance
“…Moreover, we found the latency of the left SMG was negatively correlated with the ability to name, similar to the results from a previous fMRI study (41). In a recent fNIRS study performed by Gilmore et al, the left SMG was also reported to be involved in semantic features and picture-naming tasks (42), while differences should be noted between the two studies. Gilmore et al enrolled patients with an average AQ of 67.17 (42.20-93.20), while in our present study, patients with an average AQ of 13.34 (2.6-21.7) were included.…”
Section: Cortical Activation Patterns For Language Captured By Fnirssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, we found the latency of the left SMG was negatively correlated with the ability to name, similar to the results from a previous fMRI study (41). In a recent fNIRS study performed by Gilmore et al, the left SMG was also reported to be involved in semantic features and picture-naming tasks (42), while differences should be noted between the two studies. Gilmore et al enrolled patients with an average AQ of 67.17 (42.20-93.20), while in our present study, patients with an average AQ of 13.34 (2.6-21.7) were included.…”
Section: Cortical Activation Patterns For Language Captured By Fnirssupporting
confidence: 90%
“…A disadvantage of fNIRS that is not unique to this study is that it measures signals ∼1.5-cm deep into the cortex, meaning that the contribution of subcortical structures in naming tasks in global aphasia could not be captured in this study. Nevertheless, the cortical coverage in this study was greater than in other aphasia studies to date [e.g., 64 channels in this study vs. 56 channels in Gilmore et al (42)]. Similarly, methods for managing the lesion in fNIRS studies in aphasia are still emerging.…”
Section: Limitationsmentioning
confidence: 56%
“…In this study, we found that the IFG_L of patients with aMCI had concurrent structural and functional changes, which suggested that IFG_L might be a better indicator for predicting cognitive deficits in aMCI ( Gilmore et al, 2021 ). IFG_L was related to language/semantic processing.…”
Section: Discussionmentioning
confidence: 65%
“…The activation increases in the IFG, MTG, PMC and SMG were expected due to their connection to the language network (44,45). While activations in the IFG and SMG are a typical neural correlate for picture naming (68), the PMC is associated with speech motor control in general (for a review, see Tremblay, et al (32)) but also with the prolongation and repetition of syllables (69). Notably, our additional finding in the MTG can be explained by its associated functional role in sentence generation (70,71), which was more relevant in our task (complex panorama picture description) than in the tasks implemented by other studies (reading sentences), the activation in the DLPFC can be explained by increasing working memory demands (33)(34)(35) and/or the inhibition of fluent speech (72).…”
Section: Discussionmentioning
confidence: 94%